Pemanfaatan Video Tutorial MYOB Terhadap Keterampilan Siswa dalam Mengoperasikan Aplikasi Komputer Akuntansi - Chintya Dewi Giovani; Asep Hidayat; Popon Mariam (Program Studi Pendidikan Ekonomi, FKIP Universitas Langlangbuana, 2018)
This research is about MYOB Tutorial Video utilization to improve students skills in operating computer accounting applications. This title was taken based on the lack of students skills in learning the MYOB software for Accounting Application. The reality in the field researchers found the problem that there are still many high school students in the accounting have difficulty operating the MYOB application, one of the causative factors is the limited media used in presenting interesting media and being able to clarify material that can improve students' understanding and skills in operating MYOB in the learning process. The research method used in this study is an experimental research method by comparing the skills of students who use video tutorial media and students who use the learning module media. This research uses quasi experimental method with nonequivalent control group design research design and quantitative research. The population of this study were students SMK Bina Warga Bandung XI Accounting. Data collection techniques use practical tests skill and observation of the implementation of learning.